GENERAL TRADE PARTNERSHIP PERFORMANCE OF ALBASIA WOOD IN LEUWISADENG–BOGOR - Sarah Widyatami; Bambang Juanda; Trias Andati (School of Business, IPB University (SB-IPB), 2016)
Difficulty in market information access, low prices and quality of farmers’ production, lack of facilities and infrastructure, needs of wood supply in a quick and large quantity have generated a partnership scheme which governs the farmers and industries to make a contract that binds and controls elements of production without having them. This study assessed the performance of partnership between a farmer group of “Binawarga Tani” and sawmills of UD Jaya Abadi, UD Dalfa Kamila, UD Putra Mandiri in Leuwisadeng, Bogor District. Comparative descriptive analysis states that partnership between the farmer group of